FAKTOR DAYA TARIK STIE BINANIAGA DAN KINERJA PELAYANAN MENURUT PERSEPSI MAHASISWA - Ramlan Ruvendi; Ismulyana Djan (STIE Binaniaga, 2005)
This study aims at knowing respondents’comments on variables which were assumed as STIE Binaniaga fascination is factors, and to measure service performance attributed to factors taken into account by respondents, besides to look for relation between student’s ages, study program, and semester with the level of student’s satisfaction. The number of samples used was 103 respondents which represented all students from various study programs at STIE Binaniaga. The data were processed by using statistical analysis technique parametric and non parametric such as Factor Analysis, Chi Square, Spearmen’s rho and ImportantPerformance Matrix Analysis. The results of the study showed that there were 15 variables, that were used when the candidates students choose STIE Binaniaga, and all of them were successfully proceed. From 15 variables then consists of 4 components (factors): appearance excellence, promotion, and location. Index of student’s satisfaction at STIE Binaniaga equals 3.45 (quite satisfied) and from ImportantPerformance Matrix Analysis showed that the ordinate of importance and performance fell at second kuadrant (hight importance and performance above adequate)